2020
DOI: 10.1007/s13595-020-0918-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diameter distribution errors on stand management decisions according to a simulated individual tree detection

Jari Vauhkonen

Abstract: & Key Message Tree-level forest inventory data are becoming increasingly available, which motivates the use of these data for decision-making. However, airborne inventories carried out tree-by-tree typically include systematic errors, which can propagate to objective function variables used to determine optimal forest management. Effects of under-detection focused on the smallest trees on predicted immediate harvest profits and future expectation values were assessed assuming different sites and interest rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Communicating data quality steps and detecting gaps in data quality is difficult, especially in large, transdisciplinary teams. The consequences of such errors include erroneous conclusions (Morrison 2016 ), lack of reproducibility (Peng 2011 , Powers and Hampton 2019 ), retraction (Evaristo and McDonnell 2020 ), and effects on management decisions (Vauhkonen 2020 ). A comprehensive data quality approach is needed to adequately represent both technological and cultural aspects of producing and maintaining high quality ecological data.…”
Section: Current Data Quality Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Communicating data quality steps and detecting gaps in data quality is difficult, especially in large, transdisciplinary teams. The consequences of such errors include erroneous conclusions (Morrison 2016 ), lack of reproducibility (Peng 2011 , Powers and Hampton 2019 ), retraction (Evaristo and McDonnell 2020 ), and effects on management decisions (Vauhkonen 2020 ). A comprehensive data quality approach is needed to adequately represent both technological and cultural aspects of producing and maintaining high quality ecological data.…”
Section: Current Data Quality Approachmentioning
confidence: 99%
“…Such breakdowns can also increase the risk of ill-conceived data-driven management decisions. For instance, Vauhkonen ( 2020 ) found that tree-level inventories derived from airborne methods underdetect small trees and, therefore, underpredict harvest profits, resulting in misleading future profit expectations for managers. Similarly, Brunialti and colleagues ( 2012 ) demonstrated limited comparability of lichen diversity estimates because of variability in protocol interpretation, data collector skill sets, and training procedures, which resulted in a restricted ability to monitor changes in lichen biodiversity in response to ecological drivers that would inform management.…”
mentioning
confidence: 99%
“…Moreover, a group of trees can be difficult to detect as distinct trees (Packalen et al 2013). The errors related to the detection of suppressed trees may not have a critical effect on the errors associated with predicted volumes but are surely critical shortcomings from the point of view of diameter distributions (Persson et al 2002;Vauhkonen 2020).…”
Section: Individual Tree Detectionmentioning
confidence: 99%
“…Airborne inventories are also becoming more routine and have great potential to be used to generate even tree-level data for forest modelling and decision support. Vauhkonen (2020), however, warns of the incorporation of systemic errors by this method in some forest types. As a result, under-detection of smaller classes of trees may lead to sub-optimal management decisions and losses of as much as 17% in future income.…”
mentioning
confidence: 99%